Gerhard Richter : War Cut. - Musée d'art Moderne de la ville de Paris Paris (Paris : Musée d'Art Moderne de la Ville de Paris, 2005)
Texts taken from the Frankfurter Allgemeine Zeitung of March 20 and 21, 2003 (beginning of the Iraq War)
Frans
boek
Keywords: Richter, Gerhard